Preparedness, Implications, and Administrative Responses to Public Health Emergencies in Relation to Health Security, Health Informatics, and Health Administration: An Updated Review - Aldawsari, Mabkhoot Mohammed Mabkhoot; Faris Salem bin Mohammed Al Habuban; Abdulkarim Marzooq Awad Alhejaili; Hamed Abdullah Alotaibi; Ibrahim Yahia Mohammed Aqeel; Sara Suliman Albedah; Sultan Khalid Mohammed Orayji; Tasneem Saeed Moeeni; Mosab Mohammed Sawan; Naji Saleh Alshehri; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Public health emergencies (PHEs)—arising from conflict, displacement, pandemics, and climaterelated hazards—disrupt the six healthsystem building blocks and widen inequities, particularly among women, children, older adults, people with disabilities, and lowincome groups. Primary health care (PHC) is pivotal for equitable, rapid, and communityanchored responses. Aim: To synthesize updated evidence on preparedness, impacts, and administrative responses to PHEs, with emphasis on health security, health informatics, and health administration, and to identify lessons that strengthen PHCcentred resilience. Methods: A scoping review (PRISMAScR) across major databases and grey literature (to Oct 30, 2022) included studies in English without geographic limits. Data were thematically analyzed across the PHE cycle: preparedness, impacts, response, recovery, and learning. Results: Preparedness gaps were common: workforce shortages, weak stockpiles, fragile infrastructure, unclear SOPs, and limited surveillance/incident command. Nevertheless, decentralized governance, routine simulations, and reorganized PHC improved readiness (e.g., Indonesia, Shenzhen, Japan). PHEs strained service delivery, workforce wellbeing, information systems, financing, and governance, amplifying digital and social inequities. Effective responses integrated PHC with public health, leveraged multisectoral partnerships, deployed multidisciplinary/community health teams, and scaled digital tools (telemedicine, early warning, realtime monitoring). Conclusion: Building resilient PHC requires integrated governance, sustained financing, interoperable digital health, workforce surge and support, and community engagement to ensure continuity, equity, and health security across future PHEs.